The Effect of Perceived Value, Perceived Risk, and Price on Customers Buying Intention (Case Study: Employees of Presov Electronics Company) - Naami, Abdollah; Rahimi, Zahra; Ghandvar, Parisa (International Review of Management and Marketing, 2017)
Studies have shown that the perceived value must be in the gravity center of marketers affords in perception of consumers’ behavior. In this regard, empirical studies showed that the conception of the perceived value can be useful in clarifying consumers’ behavioral decisions, because this conception is a part of a consumer behavior, Therefore, the main question for this research is whether perceived value, perceived risk, and the perceived price influence on customers’ buying intention? Thus, Beneke et al. (2015) model was used and the examined variables are perceived quality, perceived value, perceived risk, and price that were studied for customers’ buying intention. Thus, the examined statistical population of this research was central office employees of Presov Electronics Company. As all of them were 80, there was no sampling and all were included in population. The methodology was surveying and a questionnaire as a tool whose reliability was obtained 0.939 and was distributed among employees. Finally, results showed that all hypotheses were confirmed. Keywords: Price, Perceived Value, Perceived Risk, Customers Buying Intention JEL Classifications: G32, M3